Comparison efficiency of posteroanterior cephalometry and cone-beam computed tomography in detecting craniofacial asymmetry: A systematic review - Faezeh Yousefi; Elahe Rafiei; Mina Mahdian; Vahid Mollabashi; Seyedeh Shabnam Saboonchi; Seyed Mehdi Hosseini (Wolters Kluwer Medknow Publications, 2019)
Objectives: The aim of this systematic review is to compare cone-beam computed tomography (CBCT) and two-dimensional radiography in the assessment of facial asymmetry. Methods: Three valid electronic databases (PubMed, Scopus, and Web of Science) were searched for articles published from 1973 to February 2017. Hand searching was done through references of selected articles, internal thesis, and national and international conferences. The titles and abstracts obtained from the search were evaluated by reviewers according to the inclusion and exclusion criteria. Results: The established search strategy identified 2137 articles. A total of 2079 articles were from electronic search in three international databases and 58 articles from hand searching. After eliminating duplicate articles and on the basis of inclusion and exclusion criteria, 13 articles and 1 thesis entered the final analysis. Bayesian meta-analysis was done due to the heterogeneity of articles and the differences related to the methodology of the studies. According to this method, analyzing J-J landmark in two studies showed that there were no statistical differences between posteroanterior (PA) radiography and three-dimensional method with reference standard. Conclusion: The results of the study showed that there was no preference between the two techniques in measuring and diagnosing the landmarks and evaluating asymmetry. It can be concluded that in patients having problems other than asymmetry and need more information for the treatment plan, CBCT is more helpful than PA cephalometry.